Expanding Treatment Horizons: Efficacy And Safety Of Contact Lens-Assisted Collagen Cross-Linking In Thinner Corneas For Keratoconus Management In An Indian Cohort - Singh, Jitendra; Chahar, Preeti; Sharma, Pankaj; N. Gowthami, N. Gowthami; Sameera, Amatul Ali; Lateef Amrohi, Nazia (Journal of Neonatal Surgery, 2025)
Background: Keratoconus is a progressive, non-inflammatory corneal ectasia causing irregular astigmatism and visual deterioration. Corneal collagen cross-linking (CXL) is a well-established procedure to halt keratoconus progression, but conventional CXL requires a minimum corneal thickness of 400 µm after de-epithelialization. Patients with thinner corneas are thus often excluded from this effective intervention. Contact lens-assisted CXL (CACXL) was introduced to overcome this limitation, but limited data exist on its outcomes in the Indian population. Methods: This hospital-based, interventional study enrolled 75 eyes (48 patients) with progressive keratoconus and corneal thickness of 350–440 µm. After epithelial debridement, a soft contact lens soaked in 0.1% riboflavin was placed on the cornea to achieve a combined thickness ≥400 µm. Ultraviolet-A (UVA) irradiation of 30 mW/cm² was delivered for 3 minutes at 370 nm. Key parameters—minimum corneal thickness, steepest keratometry (Kmax), endothelial cell count, best-corrected visual acuity (BCVA), and manifest refraction—were recorded preoperatively and at 1, 6, and 12 months. Results: Mean corneal thickness showed no significant change at 6 and 12 months compared to preoperative values (p=0.304, p=0.433). There was no significant increase in Kmax at one-year follow-up (p>0.05). Endothelial cell counts remained stable (p>0.05). A significant improvement in BCVA was observed at 6 and 12 months (p=0.002). No major intraoperative or postoperative complications were reported. Conclusion: CACXL safely and effectively halted keratoconus progression in patients with thinner corneas, while preserving endothelial function and improving visual acuity. This approach expands treatment eligibility to corneas thinner than 400 µm and is easily adaptable using standard soft contact lenses